Hábitos alimenticios y actividad física y su relación con el estado nutricional en escolares. Escuela de Educación Básica Bahía de Caráquez Recinto Estero Lagarto, Vinces-Los Ríos, octubre 2018-abril 2019 - Llaguno Muñoz, Diego Rommel (2019)
Introduction: Currently the school feeding is characterized by a low consumption of fruits and vegetables, high consumption of fast foods with little nutritional value and decrease in the level of physical activity that generates malnutrition due to excess and deficit. General objective: To determine the relationship between eating habits and physical activity with nutritional status in schoolchildren of the "Bahia of Caraquez" Basic Education School, Estero Lagarto Campus, Vinces-Los Rios, October 2018 - April 2019. Methodology: It was a quantitative, descriptive, cross-sectional and correlational study, the sample was of 80 school students in age between 6 to 12 years, the anthropometric method was used to assess the nutritional status for its interpretation, the growth curves of the WHO; the food consumption frequency survey to identify the eating habits and the physical activity survey to know the level of physical activity. Results: The results of the study were: 53% normal, 8% thinness and 3% severe thinness, and 37% are overweight and obese. Children who consume frequent and very frequent processed foods, cereals and fats have a higher percentage of overweight and obesity, while the population that consumes very frequent fruits, vegetables and vegetables are in normality. Conclusions: When relating the nutritional status with the eating habits and the physical activity of the schoolchildren, a statistically significant relationship was found between the study variables.